Reorentasi lomba kompetensi siswa (LKS) Sekolah Menengah Kejuruan (SMK) bilingual secretary: Perlukah? - Choirul Anam; Sigit Permansah; Della Rulita Nurfaizana (Jurnal Pendidikan Ekonomi (JUPE), 2026)
The Bilingual Secretary Student Skills Competition (LKS) in Vocational High Schools (SMK) serves as an important instrument for assessing students’ readiness to enter an increasingly digitalized workforce. This study aims to describe the current implementation of LKS, particularly in terms of task formats and assessment systems, and to examine the urgency of its reorientation to align with contemporary industry demands. A descriptive qualitative approach with a case study method was employed in East Java, utilizing participatory observation, in-depth interviews, and literature review. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing and verification. The findings reveal a mismatch between current LKS task formats and industry practices, especially regarding the use of technology and digital document management. Furthermore, there is a need to enhance students’ competencies in digital skills, context-based assessment, and creative problem-solving. Therefore, reforms in task design and assessment approaches are necessary to improve the relevance of LKS as an indicator of students’ work readiness.